THU0182 Monotherapy with the jak1-selective inhibitor filgotinib displays an anti-inflammatory biomarker profile in rheumatoid arthritis patients. (15th June 2017) - Kavanaugh, A; Aa, A Van der; Jamoul, C; Li, W; Goyal, L; Pan, Y; Harrison, P; Tasset, C; Tarrant, J; Galien, R
Abstract : Background: Janus kinases (JAKs) are key proteins in the signal transduction of many cytokines and growth factors. The selective JAK1 inhibitor filgotinib (GLPG0634, GS-6034) has been evaluated in a 24-week phase 2B study (DARWIN 2) as monotherapy in active rheumatoid arthritis (RA) patients with inadequate response to methotrexate and has shown a good safety and efficacy profile 1 . Objectives: To gain insight into filgotinib mode of action as monotherapy in RA patients by analysing the impact of filgotinib on a broad panel of immune modulators in the serum. Methods: RA patients received either placebo (PBO), or filgotinib monotherapy at 50mg, 100mg or 200mg once daily (QD). Serum samples were collected at baseline, week 4 and week 12 and analysed using the 18-plex bead-based immunoassay (HSTCMAG-28SK Merck-Millipore) on BioPLEX-200 instrument to measure cytokine concentration. Median % change from baseline for biomarkers are reported for week 4 and 12. Wilcoxon rank-sum test assessed the significance of difference between filgotinib treated groups and PBO. Results: Following treatment with filgotinib at 100 mg QD and 200mg QD, there were significant reductions in cytokines important in expansion and activity of multiple T cell subsets and innate immunity compared to PBO (see Table). These changes include decreases in proinflammatory cytokines (IL-6, IL-1β, and TNFα), TH 1-related (IL-2, IFN-γ and IL-12), TH 2-related (IL-4, IL-5, and IL-13) and TH 17-related cytokines (IL-1β, IL-6, IL-17A, IL-21 and IL-23). All doses of filgotinib also reduced the B- and T-cell development cytokine IL-7. In contrast, IL-8 was not affected by filgotinib. Reductions in MIP1α, MIP1β and GM-CSF are in line with a down modulation of innate immune activity. Conclusions: Treatment of RA patients with filgotinib monotherapy resulted in significant reduction in the levels of a broad range of cytokines related to TH 1, TH 2, TH 17 and potentially B cells, as well as innate immunity. This observed anti-inflammatory activity of filgotinib is consistent with its efficacy in RA patients. References: Kavanaugh A et al. Ann Rheum Dis 2016;0:1–11.doi:10.1136/annrheumdis-2016–210105. Disclosure of Interest: A. Kavanaugh Consultant for: Galapagos, Pfizer, Abbvie, Amgen, Celgene, Janssen, Novartis, Eli Lilly, UCB, A. Van der Aa Employee of: Galapagos NV, C. Jamoul Employee of: Galapagos NV, W. Li Employee of: Gilead Sciences, L. Goyal Employee of: Gilead Sciences, Y. Pan Employee of: Gilead Sciences, P. Harrison Employee of: Galapagos NV, C. Tasset Employee of: Galapagos NV, J. Tarrant Employee of: Gilead Sciences, R. Galien Employee of: Galapagos SASU